An analysis of user-generated crisis frames: Online public responses to a tourism crisis. (January 2022) - Xie, Chaowu; Zhang, Jiangchi; Huang, Qian; Chen, Yanying; Morrison, Alastair M.
Abstract: A gap exists in the research on how online media frame a tourism crisis and the effects on travel intentions. This research proposed a basic crisis frames model for public online communications including nature (N), causes (C), processes (P), and results (R). Chinese online public opinions on the Thailand drownings in 2018 were collected and the Vector Auto-Regressive (VAR) technique explored the responses within the data. The results showed that: (1) crisis frames had a dynamic impact on negative travel intentions, and the effects and variance contributions of frames differed; (2) disturbance information produced by a negative communication incident from the destination was a factor promoting the accumulation of online public opinion; and (3) online data of public opinion and the VAR model are appropriate for research on tourism crisis information communication. This research provides new insights and a method for investigating tourism crises and dynamic responses in online communication. Highlights: Crisis frames model for public online communications includes nature, causes, processes, and results. Crisis frames have a dynamic impact on negative travel intentions. Effects and variance contributions of frames differ. Disturbance information is a factor promoting the accumulation of online public opinions. Online public opinions and the VAR model are appropriate for research about tourism crisis communication.